New age constraints on the palaeoenvironmental evolution of the late Paleozoic back-arc basin along the western Gondwana margin of southern Peru. (March 2018) - Boekhout, F.; Reitsma, M.J.; Spikings, R.; Rodriguez, R.; Ulianov, A.; Gerdes, A.; Schaltegger, U.
Abstract: The tectonic evolution of the western Gondwana margin during Pangaea amalgation is recorded in variations in the Permo-Carboniferous back-arc basin sedimentation of Peru. This study provides the first radiometric age constraints on the volcanic and sedimentary sequences of south-central eastern Peru up to the western-most tip of Bolivia, and now permits the correlation of lateral facies variations to the late Paleozoic pre-Andean orogenic cycle. The two phases of Gondwanide magmatism and metamorphism at c. 315 Ma and c. 260 Ma are reflected in two major changes in this sedimentary environment. Our detrital U-Pb zircon ages demonstrate that the timing of Ambo Formation deposition corroborates the Late Mississipian age estimates. The transition from the Ambo to the Tarma Formation around the Middle Pennsylvanian Early Gondwanide Orogeny (c. 315 Ma) represents a relative deepening of the basin. Throughout the shallow marine deposits of the Tarma Formation evidence for contemporaneous volcanism becomes gradually more pronounced and culminates around 312 - 309 Ma. Continuous basin subsidence resulted in a buildup of platform carbonates of the Copacabana Formation. Our data highlights the presence of a previously unrecognized phase of deposition of mainly fluvial sandstones and localized volcanism (281–270 Ma), which we named ´Oqoruro Formation'. This sedimentary succession was previously miss-assigned to the so-called Mitu Group, which has recently been dated to start deposition in the Middle Triassic (∼245–240 Ma). The emersion of this marine basin coincides with the onset of a major plutonic pulse related to the Late Gondwanide Orogeny (c. 260). Exhumation lead to the consequent retreat of the epeiric sea to the present-day sub-Andean region, and the coeval accumulation of the fluvial Oqoruro Formation in south eastern Peru. These late Paleozoic palaeoenvironmental changes in the back-arc basins along the western Gondwana margin of southern reflect changes in tectonic plate reorganization in a long-lived Paleozoic accretionary orogeny. Highlights: The Ambo Formation terminated around the Mississippian-Pennsylvanian boundary. The transition from Ambo Formation to Tarma Formation represents basin deepening. We describe a previously unrecognized phase of Artinskian to Roadian deposition. The basin sedimentology of southern Peru reflects two Godwanide orogenic phases.